ANALISIS TINGKAT KEPUASAN SISWA PADA PELAYANAN PERPUSTAKAAN DI SDN 2 SUKAHURIP - Krismayanti, Nayla; Nurjamaludin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of student satisfaction with library services at SDN 2 Sukahurip. The research used a quantitative descriptive method with percentage analysis. The population consisted of 40 students from grades IV and V, and the sample was 36 students selected using the Slovinformula. Data were collected through questionnaires based on service quality indicators. The results showed that 100% of students expressed dissatisfaction with the library services. This indicates that the quality of library services has not met students' expectations, particularly in terms of facilities, book collections, and staff responsiveness. Therefore, improvements are needed to enhance service quality and support students’ learning activities. Furthermore, the findings are expected to be a reference for schools in evaluating and improving library services.